Strategi Membangun Moral Dan Akhlak Anak Usia Dini : Analisis Nilai-Nilai Pendidikan Ala Rasullullah SAW - Arini Putri Sekar Ayu; Renita Khairunnisaa (PT. AHLAL PUBLISHER NUSANTARA, 2026)
Moral and ethical education in early childhood is the main foundation in shaping a child's character in the future. During this period, children are in a golden phase of development that is very sensitive to habituation and role models, so the instilling of moral and ethical values ​​needs to be carried out systematically and continuously. This study aims to analyze strategies for developing moral and ethical values ​​in early childhood based on the educational values ​​exemplified by the Prophet Muhammad (peace be upon him). The study used a qualitative approach with a literature review method of books, national and international journal articles, previous research results, and Islamic sources such as the Qur'an, hadith, and educational literature on the Prophet Muhammad (peace be upon him). Data were analyzed through the stages of reduction, presentation, and drawing conclusions. The results of the study indicate that role models, habituation, affection, polite communication, and collaboration between teachers and parents are effective strategies in developing moral and ethical values ​​in early childhood. Keywords: Morals and Ethics, Early Childhood, Islamic Education Abstrak Pendidikan moral dan akhlak pada anak usia dini merupakan fondasi utama dalam pembentukan karakter anak di masa depan. Pada periode usia dini, anak berada pada fase emas perkembangan yang sangat peka terhadap pembiasaan dan keteladanan, sehingga penanaman nilai moral dan akhlak perlu dilakukan secara sistematis dan berkelanjutan. Penelitian ini bertujuan menganalisis strategi pembangunan moral dan akhlak anak usia dini berdasarkan nilai-nilai pendidikan yang dicontohkan oleh Rasulullah SAW. Penelitian menggunakan pendekatan kualitatif dengan metode literature review terhadap buku, artikel jurnal nasional dan internasional, hasil penelitian terdahulu, serta sumber ajaran Islam seperti Al-Qur’an, hadis, dan literatur pendidikan Rasulullah SAW. Data dianalisis melalui tahapan reduksi, penyajian, dan penarikan kesimpulan. Hasil kajian menunjukkan bahwa keteladanan, pembiasaan, kasih sayang, komunikasi yang santun, serta kolaborasi antara guru dan orang tua merupakan strategi efektif dalam membangun moral dan akhlak anak usia dini. Kata kunci: Moral Dan Akhlak, Anak Usia Dini, Pendidikan Islam